PENGARUH LIGHT SLED TERHADAP KECEPATAN LARI PADA TIM FUTSAL REAL WAHID RAF JUNIOR PEKANBARU - Farisman Laia; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this study is the lack of running speed on the Real Wahid RAF Junior Pekanbaru futsal team, the players are still slow when going to attack or defend when attacked by the opposing team. The purpose of this study was to determine the effect of light sled training on running speed on the Real Wahid RAF Junior Pekanbaru futsal team. As for the population in this study is the futsal player Real Wahid RAF Junior Pekanbaru, amounting to 8 people. In the research thesampling technique used was total sampling, so the samples in this study were 8 futsal players of Real Wahid RAF Junior Pekanbaru. The instrument used to collect data was pre-test and post-test running 30 meters fast. Based on the analysis of pree-test and post-test data there was an increase of 0.71 seconds and based on statistical analysis ofinference using the t-test resulted in a tcount of 7.1 which was greater than the table of 1.860. Means tcount> ttable. So it can be concluded that the light sled training given has a positive impact on running speed on the futsal team Real Wahid RAF Junior Pekanbaru. From the results of this study it is known overall that light sled speed training is able to make a positive contribution in increasing the running speed of the futsal players on the Real Wahid RAF Junior Pekanbaru team.Key Words: Effect of Light Sled, Running Speed